Extraction of Pectin and Cellulose from Grapefruit Peels and Production of Carboxymethyl Cellulose - An, Ngo Van; Chi, Nguyen Thi Khanh; Khanh, Tran Quang; Quan, Duong Xuan; Trung, Pham Quang; Anh Thu, Ngo Hong (VNU Journal of Science: Natural Sciences and Technology, 2023)
The peels of grapefruit are a rich source of Pectin and Cellulose. This study focuses on the extraction of Pectin and Cellulose from grapefruit peels, and the production of carboxymethyl Cellulose (CMC) from extracted products. Firstly, the extraction conditions of Pectin from grapefruit peels were optimized to obtain a high yield of Pectins such as extraction time and citric acid concentration. The weight, purity, and esterification degree of Pectin were also determined. The highest yield of Pectin is 32.12% in the extraction conditions with pH 1.25 for 60 minutes at 80 o C. The Pectin product is of 84.02% purity at 29,427 g/mol of weight with 86.40% esterification degree. For extraction of Cellulose from grapefruit peels, the highest yield of Cellulose is 45.08% in the conditions with a pH of nitric acid 0.75 for 70 minutes at 90 o C. After that, the extracted Cellulose was converted to Carboxymethyl Cellulose by Monochloroacetic acid etherification. The characterization of Pectin, Cellulose, and CMC is determined through Scanning Electron Microscopy (SEM) and Infrared spectrums. The experimental results also showed that Pectin and Cellulose were successfully extracted from grapefruit peels and Carboxymethyl Cellulose was successfully produced from the extracted Cellulose.